Hadith #2954 - Sahih al-Bukhari - Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة (Sahih al-Bukhari)
Abu `Abdur-Rahman who was one of the supporters of `Uthman said to Abu Talha who was one of the supporters of `Ali, “I perfectly know what encouraged your leader (i.e. `Ali) to shed blood. I heard him saying: Once the Prophet (ﷺ) sent me and Az-Zubair saying, ‘Proceed to such-and-such Ar-Roudah (place) where you will find a lady whom Hatib has given a letter. So when we arrived at Ar-Roudah, we requested the lady to hand over the letter to us. She said, ‘Hatib has not given me any letter
Grade: Sahih

Hadith #3546 - Sahih al-Bukhari - Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة (Sahih al-Bukhari)
A man came to Ibn `Umar and asked about `Uthman and Ibn `Umar mentioned his good deeds and said to the questioner. “Perhaps these facts annoy you?” The other said, “Yes.” Ibn `Umar said, “May Allah stick your nose in the dust (i.e. degrade you)!’ Then the man asked him about `Ali. Ibn `Umar mentioned his good deeds and said, “It is all true, and that is his house in the midst of the houses of the Prophet. Perhaps these facts have hurt you?” The questioner said, “Yes.” Ibn `Um
Grade: Sahih